Implementasi Geographic Information System Pemetaan Apotek Berbasis Web Menggunakan Leafletjs - Putra, Bangbang Hartono; Rahayu, Sri; Nashrulloh, Muhammad Rikza (Jurnal Algoritma, 2024)
A Geospatial System is a platform created specifically for the administration of data that contains spatial dimensions, or in the sense of a computer system that has the capability to build, store, manage and present location information. As a government agency, the Garut District Health Service is responsible for managing policies, circulating information, supervising and recording pharmacies in the Garut area. However, until now the Health Service has not been enriched with system facilities capable of assisting the Health Service in carrying out its functions. When monitoring pharmacies, the Health Service visits the pharmacy. However, in terms of conveying information related to the geolocation of pharmacies to the public, the Health Service still does not have a special system for disseminating information related to these locations. The aim of this research is to create a web-based geospatial platform to map pharmacies in Garut city using leafletjs. The method used in this research is Rational Unified Process (RUP), the stages are inception, elaboration, construction and transition. The modeling used is Unified Modeling Language (UML) with stages using use case diagrams, activity diagrams, sequence diagrams and class diagrams. The result of this research is to produce a geographical information system for mapping pharmacies which can make it easier for the Health Service to monitor, record and inform the locations of pharmacies in Garut City. After developing a web-based geospatial platform to map pharmacies in Garut City using the Js leaflet, this research also involved black box testing to ensure that the system was functioning properly and in accordance with the expected goals. The results of the black box testing show that the geographic information system for pharmacy mapping has successfully undergone a series of feasibility tests and is able to produce the expected results.